Translation Acceptability and Readability of Food Label Made by English Department Students of UNP from English into Bahasa Indonesia - Rani Franscisca; Havid Ardi (Universitas Negeri Padang, 2019)
Acceptability and readability are the aspects of translation quality. The objective of this research is to know the translation acceptability and readability made by the students’ of English Department of UNP in translating food label from English into Bahasa Indonesia. This study used descriptive method. The data of this research is the translation product of food label made by English Department Students who take English-Indonesian Translation subject. The instruments of this study is translations test. To gain the trustworthiness of the instrument of the research was validated and the acceptability and readability were scored by involving raters. The finding of this study reveal that the score of translation acceptability and readability of food label made by the students is less acceptable but readable. The average score for the acceptability, students’ translation acquired the average score of 2.26 which means less acceptable. Meanwhile, for the aspect of readability, the average score of translation made by the students is 2.62 means readable. It can be concluded that the English Department students still need to improve their translation competence.